Dietary Trends Among Adolescents in Surakarta City During the COVID-19 Pandemic - Fathimatuzzahrah, Hanifah; Widardo, Widardo; Ayu Sari, Amelya Augusthina (Smart Medical Journal, 2023)
Introduction: Restrictions on activities outside the home due to the COVID-19 pandemic, including schools, can influence dietary profiles, especially those of adolescents. The effort to suppress COVID-19 transmission changes Adolescents’ lifestyles, physical activity, and eating behavior towards deterioration endangers their health, and increases the risk of degenerative diseases such as obesity, diabetes, and other NCDs that can exacerbate COVID-19 disease. This study aims to explore nutritional modifications during the COVID-19 pandemic in adolescents aged 15 to 19 years, compared with their usual diets before the pandemic, and identify variables that may correlate with the changes. Methods: This study used a cross-sectional design. Data were collected by online questionnaire and interviews on food intake, body mass index (BMI), and physical activity among 96 adolescents from Surakarta City. We used the Wilcoxon test and the Kruskal-Wallis test for comparative analysis.Results: The results showed that the COVID-19 pandemic modified insignificantly the dietary intake, BMI, and physical activity. In particular, we recorded and analyzed the modified consumption of main dishes (p=0,745), side dishes (p=0,082), vegetables (p=0,000), fruits (p=0,528), snacks (p=0,128), and beverages (p=0,046) using Wilcoxon's analysis (p<0,005). In addition, the Kruskal-Wallis analysis showed that gender, BMI, and physical activity had varied comparisons with dietary intake during COVID-19.Conclusion: The COVID-19 pandemic had an insignificant impact on changes in dietary intake which were not significantly affected by gender, BMI, and physical activity in adolescents in Surakarta City.